THE STRATEGY OF TRANSFORMING THE ISSYK-KUL OBLAST OF THE KYRGHYZ REPUBLIC INTO A SUPRARESILIENT SMART REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This research was carried out in the framework of the President of the KyrgyzRepublic Sooronbay Jeenbekov’s Decree as of January 11, 2019, No. 1 «On declaring 2019 theYear of Regional Development and Digitalization of the Country» and presented as a report atthe III International Round Table “Biological and Food Security, Ecology and Modern DigitalTechnologies «in Bishkek, Kyrgyzstan, September 16–17, 2019. The article also reflects thedecisions of this Roundtable regarding the creation of a smart region based on the Issyk-KulOblast
Keywords: smart region, digital government services, blockchain technology, digitalization, forecasting, supra-volatility.